Strategies for Reducing Demurrage at the Douala Container Terminals (RTC Terminal) during Importation - (:unkn) unknown (My University, 2023)
COVID-19 diverse methods and procedures of different port actors are some of the reasons for increasing demurrage for containerized goods. Demurrage is the additional charges levied by the maritime carrier on the users of its equipment (container) after the container passes the normal time in the seaport, which is 11 days in Cameroon (Douala). This study aims to investigate the main causes of increasing demurrage at the Douala container terminal and recommend strategies to reduce the increasing demurrage at the port RTC terminal (Container terminal management or Regie du Terminal a Conteneurs). This study uses a target population of 700 actors selected using a stratified random techniques in different fields linked to the international logistics chain and the Douala port in particular. Moreover a total of 490 participants responded to the questionnaire distributed to them. Descriptive statistics such as table and pie chart were used to analyze the data collected during the research. Findings demonstrated that the activities of the different actors involved in the logistics chain, namely the customs administrators, customs brokers, importers, shipping line exporters, PAD (Douala Autonomous Port) and other actors such as Society General de Surveillance (SGS), Cameroon Customs Information System (CAMCIS) and RTC Terminal are the main causes of the increased demurrage at the Douala port. The study recommends, amongst others, eliminating public holidays and weekends by shipping line when counting the demurrage days at the Douala port. Also we recommend that, the demurrage days should only start when the manifest is visible to all the actors, which is not the case. Equally, the government should impose the demurrage charge on the actors, which are the principal cause of demurrage at the port. It should be noted that with the implementation of the above recommendations by the different actors, demurrage will reduce in the Douala port and many African countrie
Keywords: African Research